2014
DOI: 10.1063/1.4861068
|View full text |Cite
|
Sign up to set email alerts
|

Hilbert statistics of vorticity scaling in two-dimensional turbulence

Abstract: In this paper, the scaling property of the inverse energy cascade and forward enstrophy cascade of the vorticity filed ω(x, y) in two-dimensional (2D) turbulence is analyzed. This is accomplished by applying a Hilbert-based technique, namely Hilbert-Huang transform, to a vorticity field obtained from a 81922 grid-points direct numerical simulation of the 2D turbulence with a forcing scale kf = 100 and an Ekman friction. The measured joint probability density function p(C, k) of mode Ci(x) of the vorticity ω an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Theoretically, Nam et al (2000) found that the Ekman friction leads to an intermittent forward enstrophy cascade (Bernard 2000), which has been verified indirectly by studying the passive scalar field, instead of the vorticity field (Boffetta et al 2002). More recently, this claim has been confirmed by Tan et al (2014) using Hilbert spectral analysis. A log-Poisson model without justice is proposed to fit the forward enstrophy cascade scaling exponent, see details in Tan et al (2014).…”
Section: D Turbulence Velocitymentioning
confidence: 87%
See 2 more Smart Citations
“…Theoretically, Nam et al (2000) found that the Ekman friction leads to an intermittent forward enstrophy cascade (Bernard 2000), which has been verified indirectly by studying the passive scalar field, instead of the vorticity field (Boffetta et al 2002). More recently, this claim has been confirmed by Tan et al (2014) using Hilbert spectral analysis. A log-Poisson model without justice is proposed to fit the forward enstrophy cascade scaling exponent, see details in Tan et al (2014).…”
Section: D Turbulence Velocitymentioning
confidence: 87%
“…For the last few decades, numerous experiments and numerical simulations have been devoted to verifying the abovementioned forward and inverse cascades (Kellay et al 1998(Kellay et al , doi:10.1088(Kellay et al /1742(Kellay et al -5468/2015/06/P06018 Rutgers 1998, Bruneau and Kellay 2005, Bernard et al 2006, Boffetta 2007, Falkovich and Lebedev 2011, Tan et al 2014 with a partial verification of the theory by Kraichnan. For example, Boffetta and Musacchio (2010) performed a very high resolution numerical simulation, up to a grid number N = 32 768 2 .…”
Section: D Turbulence Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…in which r N (t) is a residual. The extracted C i (t) can be considered as an 'intrinsic' oscillation structure of the turbulence, e.g., a vortex in the statistics sense [45]. Based on the dyadic filter bank property of the EMD methodology, the number N of the IMF mode is limited as…”
Section: The Hilbert-huang Transform and Two-scale Correlation 21 The...mentioning
confidence: 99%
“…Lagrangian turbulence [24], river turbulence [29], vorticity statistics in two-dimensional turbulence [45], etc, to characterize the intermittent nature of these processes [23]. For details on this methodology, we refer to [22,21,18,28,23,27,26].…”
Section: The Hilbert-huang Transform and Two-scale Correlation 21 The...mentioning
confidence: 99%